The shaman illuminator as a cosmic bricoleur and the child's Indian look in children's theater (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2022)
This text proposes the analysis of the scenic illuminator as a shaman and the child as a spectator, both with their respective Indian eyes, within an artistic or imaginary construction that is a bricolage. The reception of the child in a children's show, visually selecting everything they want from the scene, engenders a new universe of understanding of what they witness in the theater. This deals with the relationship between the shaman-illuminator as a cosmic bricoleur and the reception of the child audience, based on a lucid dream pact established between them through a rigorous Indian gaze, the gaze of the bricoleur, which creates artistic or spiritual artifacts that refunctionalize and reorder the world in that spectacle.
Keywords: scenic lighting; shamanism; children's theater; bricolage